Penerapan Revolusi Industri 4.0 Pada UMKM Batik Di Desa Tegalsari Kecamatan Ambulu Kabupaten Jember - Antika, Elly; Kurniawati, Dewi; Rakhmat, Hariyono; Setyo Wibowo, Nugroho (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Batik, developed by Mrs. Lestari, is a business with a typical motif of the Ambulu coast and the Motif of Tobacco Jember. This written batik business was named Rezti's Batik in Tegalsari Ambulu Village, Jember, and had 18 employees, two of whom had disabilities. This written batik product is well known to the public, even abroad. But Batik Resti has obstacles when meeting its customers because the process of drying batik staining still relies on the sun's heat. During the rainy season, orders often can not be on time because of the unfinished coloring process. The implementation of community service in the application of community science and technology (PIM) solves this partner problem by designing and making batik dryer spaces to increase productivity, optimize the use of social media, and product development. The batik dryer is built with an automatic temperature controller that can be adjusted according to the needs of the batik drying process. Batik dryers use standard operating procedures (SOP) for operational equipment needs. This batik dryer can dry 14 pieces of cloth in each process. Training in making social media content and product development training can increase the knowledge and skills of Batik MSMEs.